Preliminary surveys of the endangered Lord Howe Island cockroach Panesthia lata (Blattodea: Blaberidae) on two islands within the Lord Howe Group, Australia. Issue 2 (11th July 2017) - Carlile, Nicholas; Priddel, David; O'Dwyer, Terence
Abstract: Little is known of the Endangered Lord Howe Island Cockroach Panesthia lata Walker, 1868, other than that it disappeared from Lord Howe Island following the introduction of ship rats Rattus rattus (Linnaeus, 1758) in 1918. With a rodent‐eradication programme being planned for Lord Howe Island, an opportunity exists to reintroduce P. lata once rodents have been removed. Previous brief surveys of other islands within the Lord Howe Group have found that P. lata still occurs on some of these islands. In this study, further surveys were conducted on two of those islands (Blackburn and Roach) to gain a better understanding of the distribution and abundance of P. lata there and to investigate potential survey techniques. Brief observations were also made of the behaviour and ecology of the species. Extrapolation from survey plots showed that although 60% of the estimated population of 10 000 individuals on Blackburn Island were living beneath the sole Banyan Ficus macrophylla Desf. tree, P. lata was widely distributed across the island, utilising both native and exotic vegetation, including the introduced Rhodes Grass Chloris gayana Kunth. On Roach Island, the bulk of the estimated population of 3500 individuals occurred within Leafy Flat Sedge Cyperus lucidus R. Br. habitat. Panesthia lata seemingly spends considerable time sheltering within refuges rather than foraging on the surface; consequently, population estimates based on surface counts are underestimates. Improving either the accuracy or precision of these counts risks damaging individuals and their habitat. Mark‐recapture techniques were not applicable for assessing the abundance of this species, but trials of novel attraction stations indicated that such devices could be useful for monitoring distribution and gross fluctuations in population size. Panesthia lata appears to feed on any dead vegetation, but primarily leaves. Individuals were relatively sedentary overnight, sheltering by day under any object that provided the appropriate microenvironment. Soil characteristics in areas where P. lata sheltered were significantly modified, suggesting that this species may play an important role in soil conditioning and nutrient cycling. Maintaining the rodent‐free status of islands on which P. lata occurs is a high priority for this species.